1970
DOI: 10.1002/dev.420030303
|View full text |Cite
|
Sign up to set email alerts
|

Studies of undernutrition in the young rat: Methodological considerations

Abstract: Gales b urg, IllinoisPlaut, S. Michael (1970). Studies of Undernutrition in the Young Rat: Methodological Considerations. Developmental Psychobiology, 3 ( 3 ) : 157-1 67. Three techniques are generally described as creating a state of undernutrition in the young rat: large litter size, periodic mother-litter separation, and early weaning. Evidence from studies of maternal behavior and early experience suggests that many of the effects seen in "nutritional deprivation" experiments may be due, in part, to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1973
1973
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…It is also important to recognize that there may be behavioral measures other than those used here which are more sensitive to nutritional effects, and this should be addressed in future research. Another concern is that manipulation of litter size affects not only pup nutrition but also the nature of the interaction between dam and offspring (Plaut, 1970;Priestnall, 1972;Crnic, 1980), and presumably between offspring themselves. It is interesting to note that, although pups reared in litters of 3 were the heaviest in the study, those reared in litters of 5 had the most advanced behavioral score.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to recognize that there may be behavioral measures other than those used here which are more sensitive to nutritional effects, and this should be addressed in future research. Another concern is that manipulation of litter size affects not only pup nutrition but also the nature of the interaction between dam and offspring (Plaut, 1970;Priestnall, 1972;Crnic, 1980), and presumably between offspring themselves. It is interesting to note that, although pups reared in litters of 3 were the heaviest in the study, those reared in litters of 5 had the most advanced behavioral score.…”
Section: Discussionmentioning
confidence: 99%
“…The function of this system and levels of plasma corticosteroids have repeatedly been related to levels of emotionality (Bronson & Eleftheriou, 1963;Howard, 1973;Levine & Mullins, 1968). Although the hightened emotionality found in animals from large litters may be the consequence of differential functioning of the adrenocortical system, the contributions of nutritional and maternal stress factors have not yet been determined (Plaut, 1970).…”
Section: Emotionalitymentioning
confidence: 99%
“…The methods used to produce undernutrition in rats are accompanied by changes in mother-pup interaction (8)(9)(10)(11)(12) and it has been proposed that changes in maternal behavior tend to minimize the effects of undernutrition on offspring growth and development (13,14). Other studies have indicated that the changes in maternal behavior cause either beneficial effects (15) or no effect on the later behavior of offspring (16,17).…”
Section: Introductionmentioning
confidence: 99%